Expediente e Nominata - REVER, Redação (REVER: Revista de Estudos da Religião, 2021)
Avaliadores desta edição: Alzirinha R. de Souza (UNICAP, Pernambuco-PE); Ana Paula R. Cavalcanti (UFPB, João Pessoa-PB); Ana Rosa da Silva (PUC-Campinas, Campinas-SP); Arilson S. Oliveira (UFCG, Campina Grande-PB); Carlos André Silva de Moura (UPE, Recife-PE); Diego G. Klautau (PUC Minas, Belo Horizonte-MG); Drance Elias da Silva (UNICAP, Pernambuco-PE); Edward J. B. Neves MacRae (UFBA, Salvador-BA); Fabio Scorsolini-Comin (USP, São Paulo-SP); Fernanda S. Cardoso (UNIMONTES, Montes Claros-MG); Frederico Pieper (UFJF, Juiz de Fora-MG); Geraldo Luiz de Mori (FAJE, Belo Horizonte-MG); Johnni Langer (UFPB, João Pessoa-PB); José Botelho Moniz (UCP, Portugal); José Luiz Moraes Franco (IFPA, Tucuruí-PA); Karla Denise Martins (UFV, Viçosa-MG); Leandro Vilar Oliveira (autónomo, João Pessoa-PB); Lino Rampazzo (UNISAL, São Paulo-SP); Marcelo Mercante (autónomo, São Paulo-SP); Murilo M. Vilaça (FIOCRUZ, Rio de Janeiro-RJ); Nestor Figueiredo (UFPB, João Pessoal-PB); Omar L. P. F. Sales (PUC Goiás, Goiânia-GO); Rafael Shoji (autônomo, São Paulo-SP); Ricardo Gonçalves Castro (FSDB, Manaus-AM); Richard Gonçalves André (UEL, Londrina-PR); Ron Cole-Turner (PTS, Pittsburgh-EUA); Scott Randall Paine (UnB, Brasília-DF); Selma de Sousa Brito (SEMED Salvaterra-PA); Silas Guerriero (PUC-SP, São Paulo-SP); Tiago T. Contiero (CEUCLAR, Montes Claros-MG); U. R. Kleinhempel (Bayernkolleg-SW, Alemanha); Zuleica D. P. Campos (UNICAP, Pernambuco-PE)